2008
DOI: 10.1534/genetics.108.090134
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Complex Traits in Teosinte (Zea maysssp.parviglumis): New Evidence From Association Mapping

Abstract: Previous association analyses showed that variation at major regulatory genes contributes to standing variation for complex traits in Balsas teosinte, the progenitor of maize. This study expands our previous association mapping effort in teosinte by testing 123 markers in 52 candidate genes for association with 31 traits in a population of 817 individuals. Thirty-three significant associations for markers from 15 candidate genes and 10 traits survive correction for multiple testing. Our analyses suggest severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 49 publications
3
79
0
Order By: Relevance
“…Variants in zap1 were associated with ear length in teosinte (Weber et al 2008); our results suggest some functional variation at this locus passed through the domestication bottleneck and remains in maize or new functional variants have arisen within maize. Haplotypes at candidate gene gt1 were also associated with a small amount of shank length variation in maize.…”
Section: Heritability and Polygenic Variationmentioning
confidence: 64%
See 2 more Smart Citations
“…Variants in zap1 were associated with ear length in teosinte (Weber et al 2008); our results suggest some functional variation at this locus passed through the domestication bottleneck and remains in maize or new functional variants have arisen within maize. Haplotypes at candidate gene gt1 were also associated with a small amount of shank length variation in maize.…”
Section: Heritability and Polygenic Variationmentioning
confidence: 64%
“…Furthermore, teosinte "ears" are small, with kernels arranged in a distichous (two-ranked) pattern on the ear axis, compared to large ears of maize that typically have from 8 to .20 rows of kernels in four or more ranks. Several major QTL and in some cases, the specific genes, controlling these differences between maize and teosinte have been identified (Clark et al 2003;Doebley 2004;Briggs et al 2007;Weber et al 2008).The strong directional selection that occurred during the domestication of maize from teosinte reduced genetic diversity most strongly at key genes controlling domesticationrelated traits. Despite the severe bottleneck that occurred during domestication and strong selection for the maize plant type, standing variability in cob length, kernel row number, and shank length can be observed among maize breeding lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest evidence for this comes from study of the gene encoding the teosinte branched TCP TF whose activity has influenced (negatively) the degree of branching in the transition during domestication from teosinte to maize, largely through changes in its expression pattern (Doebley et al, 1997;Wang et al, 1999;Lukens and Doebley, 2001;Doebley, 2004). Some studies, such as those of Weber et al (2007), have subsequently shown strong association of major traits distinguishing species to be associated with regulatory genes (although the definition of a regulatory gene in this case was not restricted to TFs), with three out of the five genes showing strong associations between regulatory genes and major trait variation in standing populations of teosinte, encoding TFs.…”
Section: Are Regulatory Changes In Genes Encoding Tfs the Predominantmentioning
confidence: 99%
“…Consequently, what started as a relatively robust proposal has more recently been watered down, such that the definition of regulatory genes includes genes involved in signal transduction (Weber et al, 2007). Originally Doebley and Lukens suggested that evolution was more likely to occur through changes in the expression of genes involved in transcriptional regulation than those involved in sig-naling pathways; an argument based on the idea that signaling components operate upstream of transcriptional regulators, so that changes in the expression of signaling components were more likely to cause pleiotropic effects (and therefore had many more ways of being severely deleterious).…”
Section: Is Evolution Of Cis-acting Regulation Predominant Regardlesmentioning
confidence: 99%